Intravascular stents: a new technique for tissue processing for histology, immunohistochemistry, and transmission electron microscopy. Issue 5 (1st November 1998) - Malik, N; Gunn, J; Holt, C M; Shepherd, L; Francis, S E; Newman, C M H; Crossman, D C; Cumberland, D C
Abstract : Background: Study of the vascular response to stent implantation has been hampered by difficulties in sectioning metal and tissue without distortion of the tissue stent interface. The metal is often removed before histochemical processing, causing a loss of arterial architecture. Histological and immunohistochemical sections should be 5 μm with an intact tissue stent interface. Objectives: To identify the most suitable cutting and grinding equipment, embedding resin, and slides for producing thin sections of stented arteries with the stent wires in situ for histological, immunohistochemical, and transmission electron microscopic (TEM) analyses. Methods: 20 balloon stainless steel stents were implanted in the coronary arteries of 10 pigs. Twenty eight days later the stented arterial segments were excised, formalin fixed, embedded in five different resins (Epon 812, LR white, T9100, T8100, and JB4), and sectioned with two different high speed saws and a grinder for histological, immunohistochemical, and TEM analyses. Five stented human arteries were obtained at necropsy and processed using the best of the reported methods. Results: The Isomet precision saw and grinder/polisher unit reliably produced 5 μm sections with most embedding resins; minimum section thickness with the horizontal saw was 400 μm. Resin T8100, a glycol methacrylate, enabled satisfactory sectioning, grinding, and histological (toluidine blue, haematoxylin and eosin, and trichromatic and polychromatic stains) and immunohistochemical analyses (α smooth muscle actin, von Willebrand factor, vimentin, proliferating cell nuclear antigen, and CD68 (mac 387)). T9100 and T8100 embedded stented sections were suitable for ultrastructural examination with TEM. Stented human arterial sections showed preserved arterial architecture with the struts in situ. Conclusion: This study identified the optimal methods for embedding, sawing, grinding, and slide mounting of stented arteries to achieve 5 μm sections with an intact tissue metal interface, excellent surface qualities, histological and immunohistochemical staining properties, and suitability for TEM examination. The technique is applicable to experimental and clinical specimens.